PELATIHAN PEMBUATAN RENCANA PEMBANGUNAN JANGKA MENENGAH DESA (RPJMDES) DI KECAMATAN SIDOMULYO KABUPATEN LAMPUNG SELATAN - Ekana P.S, Yana; Krisbintoro, R. Sigit; Kurniawan, Robi Cahyadi; Indrajat, Himawan (Prosiding Pengabdian FISIP Unila, 2012)
The event was held at the District Office Sidomulyo South Lampung regency with two methods of activities, lectures and discussions as well as practical training RPJMDesa creation. The conclusions obtained from the comparison of the results of pre-test to post-test does not necessarily be used as the foundation of the legitimacy and validity of changes in knowledge, attitudes and behaviors that are expected due to the characteristics of village officials who attend counseling peemrintahan is very diverse. The condition can actually be better than at the time of counseling done, or maybe even no better than what comes out of the post-test assessment results in this extension. Guidance on procedures RPJM Sidomulyo village in the district is the first step to the basic thinking strategic step what needs to be done in order to continue this outreach in the form of other service activities. This is to complete the transformation not only of knowledge, but also attitudes and behaviors. Keywords: Rural Development, Planning and Development.